2018
DOI: 10.1186/s12889-018-5441-6
|View full text |Cite
|
Sign up to set email alerts
|

Flu vaccination among patients with diabetes: motives, perceptions, trust, and risk culture - a qualitative survey

Abstract: BackgroundVaccination against seasonal influenza (SIV) is recommended for patients with diabetes, but their vaccination coverage is unsatisfactory in France and elsewhere. This qualitative survey of people with diabetes sought to explore 1) the extent to which SIV-related behaviour is more or less automatic; 2) reasons they choose/reject SIV; 3) their trust/distrust in authorities, science, and medicine.MethodsWe conducted semi-structured in-depth interviews of 19 adults with diabetes in 2014. We recruited the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
55
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(72 citation statements)
references
References 35 publications
7
55
0
Order By: Relevance
“…Our results demonstrate, consistently with previous findings, that people with diabetes have mainly stable SIV behaviors. 6,7,14 The finding that the probability of remaining vaccinated (0.91) was significantly higher than that of remaining unvaccinated (0.83) is somewhat encouraging, even though the order of magnitude of these probabilities did not differ notably. Nonetheless, the probabilities of behavioral shifts were non-negligible in each group and higher for starting to vaccinate than for stopping it.…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations
“…Our results demonstrate, consistently with previous findings, that people with diabetes have mainly stable SIV behaviors. 6,7,14 The finding that the probability of remaining vaccinated (0.91) was significantly higher than that of remaining unvaccinated (0.83) is somewhat encouraging, even though the order of magnitude of these probabilities did not differ notably. Nonetheless, the probabilities of behavioral shifts were non-negligible in each group and higher for starting to vaccinate than for stopping it.…”
Section: Discussionmentioning
confidence: 89%
“…These findings confirm the key role of doctors in promoting SIV among at-risk patients. 6,12,21 Previous studies have shown that patients trust their physicians strongly 7 and that these professionals can play an important role in improving patients' knowledge and decision-making process about SIV. 22,23 The absence of any similar effect for endocrinologists and cardiologists, however, suggests that these specialists might be missing some opportunities to promote SIV.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As in previous studies [ 18 ], we also found that mothers were more often vaccine hesitant than fathers, perhaps because they are often more involved in the medical follow-up of their children. Finally, in EP, health concerns and chronic disease have already been described as motives for attributing a low priority to or refusing influenza vaccination [ 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%